Applications of X-Ray Holography - Shi, Bingjun; Fu, Yuan; Yang, Yan (International Journal of Optics, 2021)
X-ray holography is widely used in material, biology, and industry fields due to its potential to measure the microstructure and dynamic change of objects. In this review, the principle of X-ray holography and the development of this technology in different application fields are systematically summarized and discussed. Through analyzing the advancement of X-ray sources and recording medium, the research and development direction of X-ray holography are prospected and the overview on current strategies of novel X-ray holography is presented. It is proved that X-ray holography, as a powerful nondestructive measurement method, can be applied to a wide range of objects.